"Let us rebuild our country": Migration-development scenarios in Ghana - Nauja Kleist (Danish Institute for International Studies (DIIS), 2011)
In recent years, there has been a reconfiguration of the relationship between states and international migrants. From an overall perception of migration as a problem to be solved, a number of international development agencies, policy makers, and academics are taking the position that migration contributes to national development - if well managed. This aspiration indicates the (re-)discovery of non-resident citizens or former citizens as populations to be governed by their states of origin. The implications of this aspiration are examined in this working paper, focusing on migration-development scenarios in Ghana. The paper is inspired by anthropological and critical development studies on statecraft and public policy, approaching migration-development scenarios as a cultural and political object of study. Using the theatrical metaphor of scenario, it analyzes actually implemented policies as well as policy visions and debates, focusing on the underlying narratives and imaginaries of how migration and development are interlinked and can be governed. The paper argues that the Ghanaian migration-development policy initiatives are attempts to symbolically include international migrants in the nation and to constitute them as a patriotic and governable population, ascribing a central role to the state in facilitating and governing international migration for national development. The policies thereby send a signal to migrants as well as to other states of the Ghanaian state's ambition to perform sovereignty in the sense of controlling subjects and resources - even if they are located outside the national territory. Migration-development initiatives thus also function as a policy spectacle where the government signals that it is taking its responsibility as a migrant-sending state seriously.
Keywords: 300; Internationale Migration; Migrationspolitik; Entwicklungspolitik; Ghana